No Influence of Type 2 Diabetes on Chronic Inflammation and Oxidative Stress in Obese Patients - Adriana Florinela CĂTOI; Alina Elena PÂRVU; Adriana MUREŞAN; Cristina BIDIAN; Cornel CĂTOI; Ioana Delia POP (Notulae Scientia Biologicae, 2014)
Obesity per se carries the features of chronic inflammation and oxidative stress that interrelate in a complex network and exert an important role in the onset of several complications such as type 2 diabetes, atherosclerosis and cardiovascular events. On the other hand, it seems that hyperglycemia per se as well as insulin resistance (independent of hyperglycemia), both induce increased oxidative stress. The aim of our study was to analyze proinflammatory and oxidative stress markers in obese patients with and without type 2 diabetes and to verify the hypothesis that type 2 diabetes associated with obesity would promote a higher chronic inflammation and oxidative stress state as compared to obesity alone. We found no differences between the two groups of patients regarding chronic inflammation and oxidative stress markers. Therefore we may conclude that there is no influence of type 2 diabetes on chronic inflammation and oxidative stress in obese patients.